2016
DOI: 10.1103/physrevb.94.104509
|View full text |Cite
|
Sign up to set email alerts
|

Lattices of double-quanta vortices and chirality inversion inpx+ipysuperconductors

Abstract: We investigate the magnetization processes of a standard Ginzburg-Landau model for chiral pwave superconducting states in an applied magnetic field. We find that the phase diagram is dominated by triangular lattices of doubly quantized vortices. Only in close vicinity to the upper critical field, the lattice starts to dissociate into a structure of single-quanta vortices. The degeneracy between states with opposite chirality is broken in a nonzero field. If the magnetization starts with an energetically unfavo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 61 publications
(120 reference statements)
7
29
0
Order By: Relevance
“…Third, Ichioka et al [46] used the time-dependent Ginzburg-Landau theory to study the magnetization process and found that with increasing magnetic fields, the domain walls move so that the unstable domains shrink to vanishing size, and the single-domain structure is realized at higher fields. Along these lines there are theories of doubly quantized vortices and other exotic behaviours that may lead to a broken field with nonzero chirality degeneracy [47,48]. Note that compared to the first proposal, chiral domain wall pinning is not emphasized, which to some extent suggests pinning by domains themselves and is probably more relevant to our observations here.…”
Section: Discussionmentioning
confidence: 58%
“…Third, Ichioka et al [46] used the time-dependent Ginzburg-Landau theory to study the magnetization process and found that with increasing magnetic fields, the domain walls move so that the unstable domains shrink to vanishing size, and the single-domain structure is realized at higher fields. Along these lines there are theories of doubly quantized vortices and other exotic behaviours that may lead to a broken field with nonzero chirality degeneracy [47,48]. Note that compared to the first proposal, chiral domain wall pinning is not emphasized, which to some extent suggests pinning by domains themselves and is probably more relevant to our observations here.…”
Section: Discussionmentioning
confidence: 58%
“…This is important to ensure that vortex matter do not interact with the domain boundaries and thus that the obtained configurations are not artifacts of boundary interactions. In particular, in the results that are displayed below, the numerical grid is larger than the displayed region which are close up views of the regions carrying vortices [35]. Note also that here we are interested in the physical properties of the vortex matter, such as intervortex forces, rather than magnetization process.…”
Section: Vortices In the Vicinity Of The S + Is Region Physics Bmentioning
confidence: 96%
“…For that purpose, the vortices are induced only by the initial configuration of the phase winding. For further details on the numerical methods employed here, see for example the related discussion in [20]. Figure 2 shows the numerically calculated (isolated) vortex solutions in the vicinity of the impurity-induced crossover, in the case of a two-band superconductor with nearly degenerate bands and weak repulsive interband pairing interaction.…”
Section: Structural Transition Of Vortex Coresmentioning
confidence: 99%